Towards gender-inclusive innovation: Assessing local conditions for agricultural targeting - López, Diana E.; Frelat, Romain; Badstue, Lone B. (2022)
The importance of gender norms in agricultural innovation processes has been recognized. However, the operational integration of these normative issues into the innovation strategies of agricultural interventions remains challenging. This article advances a replicable, integrative research approach that captures key local conditions to inform the design and targeting of gender-inclusive interventions. We focus on the gender climate across multiple contexts to add to the limited indicators available for assessing gender norms at scale. The notion of gender climate refers to the socially constituted rules that prescribe men’s and women’s behaviour in a specific geographic location—with some being more restrictive and others more relaxed. We examine the gender climate of 70 villages across 13 countries where agriculture is an important livelihood. Based on data from the GENNOVATE initiative we use multivariate methods to identify three principal components: ‘Gender Climate’, ‘Opportunity’ and ‘Connectivity’. Pairwise correlation and variance partitioning analyses investigate the linkages between components. Our findings evidence that favourable economic or infrastructure conditions do not necessarily correlate with favourable gender normative conditions. Drawing from two case-study villages from Nepal, we highlight opportunities for agricultural research for development interventions. Overall, our approach allows to integrate local knowledge about gender norms and other local conditions into the planning and targeting strategies for agricultural innovation.